Hábitos de estudio y rendimiento académico en estudiantes de segundo de secundaria de una institución educativa del Callao - Ortega Mollo, Verónica (2012)
The present investigation was to determine the relationship between study habits and academic performance of students in the second grade of secondary education in a public school district of Callao, during the academic year 2009. The study was developed using a quantitative, descriptive, correlational design. The sample was not random type available consisting of 59 students. The data collection instruments used were the Study Habits Inventory CASM-85 Revision 2005 prepared by Luis Alberto Vicuna Peri (1985) which assesses five dimensions: form of study, task resolution, test preparation, listening as the class and accompanying the study, besides the Consolidated Assessment Act Basic Education Level Secondary Education 2009. The research results demonstrate the existence of a direct, high and significant levels between study habits and academic achievement levels of students in the second grade of secondary education, highlighting the size and resolution of preparation tasks testing.